Analysing avian eggshell pigments with Raman spectroscopy - Thomas, Daniel B; Hauber, Mark E; Hanley, Daniel; Waterhouse, Geoffrey I N; Fraser, Sara; Gordon, Keith C (The Journal of experimental biology, 2015)
Avian eggshells are variable in appearance, including coloration. Here, we demonstrate that Raman spectroscopy can provide accurate diagnostic information about major eggshell constituents, including the pigments biliverdin and protoporphyrin IX. Eggshells pigmented with biliverdin showed a series of pigment-diagnostic Raman peaks under 785 nm excitation. Eggshells pigmented with protoporphyrin IX showed strong emission under 1064 nm and 785 nm excitation, whereas resonance Raman spectra (351 nm excitation) showed a set of protoporphyrin IX informative peaks characteristic of protoporphyrin IX. As representative examples, we identified biliverdin in the olive green eggshells of elegant crested tinamous (Eudromia elegans) and in the blue eggshells of extinct upland moa (Megalapteryx didinus). This study encourages the wider use of Raman spectroscopy in pigment and coloration research and highlights the value of this technique for non-destructive analyses of museum eggshell specimens.
Keywords: Animals; Egg Shell; Birds; barva; Biliverdin; Protoporphyrins; Chemical analysis; Pigments, Biological; Biliverdine; Color; Ramanova spektroskopie; biologické pigmenty; Protoporphyrin IX; ptáci; protoporfyriny; vaječná skořápka; Tinamou; Non-destructive; Spectrum Analysis, Raman; biliverdin; zvířata; Moa